2022
DOI: 10.3389/fphar.2021.819482
|View full text |Cite
|
Sign up to set email alerts
|

Red Yeast Rice for Hyperlipidemia: A Meta-Analysis of 15 High-Quality Randomized Controlled Trials

Abstract: Background: RYR is a commonly used lipid-lowering dietary supplements in Asian and European countries, showing considerable benefits and low toxicity. This quantitative study aims to present high-quality evidence regarding the efficacy and safety of RYR in treating hyperlipidemia, in order to promote its clinical application.Methods: PubMed, embase, and Cochrane Central Register of Controlled Trials databases were systematically searched, and high-quality randomized controlled trials comparing RYR with non-RYR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…A 2021 meta-analysis of 15 high-quality randomized controlled trials (mostly using doses of 600–2400 mg twice daily) involving 1012 subjects showed that RYR significantly decreased LDL-C versus placebo (mean difference [MD] −35.82 mg/dL; 95% confidence interval [CI] −43.36, −28.29 [ p < 0.00001]), with no significant difference versus other statins (simvastatin 20 mg/d, pravastatin 40 mg/d, or rosuvastatin 10 mg/d) with an MD of 1.89 mg/dL (95% CI −7.93, 11.71 [ p = 0.71]) [ 11 ]. RYR significantly increased HDL-C versus placebo (MD 3.47 mg/dL; 95% CI 0.94, 6.00 [ p = 0.007]) to a similar degree as other statins (MD 2.50 mg/dL; 95% CI −4.21, 9.22 [ p = 0.46]).…”
Section: Effect Of Ryr On Ldl-c Plasma Level and Estimated Risk Of Ascvdmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2021 meta-analysis of 15 high-quality randomized controlled trials (mostly using doses of 600–2400 mg twice daily) involving 1012 subjects showed that RYR significantly decreased LDL-C versus placebo (mean difference [MD] −35.82 mg/dL; 95% confidence interval [CI] −43.36, −28.29 [ p < 0.00001]), with no significant difference versus other statins (simvastatin 20 mg/d, pravastatin 40 mg/d, or rosuvastatin 10 mg/d) with an MD of 1.89 mg/dL (95% CI −7.93, 11.71 [ p = 0.71]) [ 11 ]. RYR significantly increased HDL-C versus placebo (MD 3.47 mg/dL; 95% CI 0.94, 6.00 [ p = 0.007]) to a similar degree as other statins (MD 2.50 mg/dL; 95% CI −4.21, 9.22 [ p = 0.46]).…”
Section: Effect Of Ryr On Ldl-c Plasma Level and Estimated Risk Of Ascvdmentioning
confidence: 99%
“…While RYR significantly reduced TC versus placebo (MD −37.43 mg/dL; 95% CI −47.08, −27.79 [ p < 0.00001]), it was less effective than other statins (MD 12.24 mg/dL; 95% CI 2.19, 22.29 [ p = 0.02]). For triglycerides, significant decreases were seen for RYR versus placebo (MD −20.65 mg/dL; 95% CI −35.60, −5.70 [ p = 0.007]) and versus other statins (MD −19.90 mg/dL; 95% CI −32.22, −7.58 [ p = 0.002]) [ 11 ].…”
Section: Effect Of Ryr On Ldl-c Plasma Level and Estimated Risk Of Ascvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses of red yeast rice identified significant improvements in LDL-C, TC and TG compared to placebo in dyslipidaemic patients. [36,37,95] Our review also found that some lactofermented foods, [53,63,76] jangs, [67,72,74] tempeh, [58][59][60] brown rice lees [64] and fermented soy powder [69] significantly improved lipid parameters compared to controls.…”
Section: Discussionmentioning
confidence: 55%
“…[18,33,34] However, as these reviews did not use systematic review methodology, many existing clinical trials of BFFs were not identified. On the other hand, we found several up-to-date systematic reviews/ meta-analyses of randomised controlled trials (RCTs) investigating the impact of red yeast rice/ monacolin/ xuezhikang [35][36][37][38][39] or vinegar [40][41][42][43][44][45] on metabolic parameters; these RCTs were thus excluded during abstract screening to prevent the waste of resources. [46] We have undertaken a systematic review of RCTs administering other BFFs to participants with T2DM, MetS, obesity, or other MetS components.…”
Section: Introductionmentioning
confidence: 99%